The ALBA constitutional project and political representation - DÍAZ DE VALDÉS JULIÁ, JOSÉ MANUEL; VERDUGO RAMÍREZ, SERGIO (My University, 2019)
Abstract After the Cold War era, significant constitutional changes took place in Latin America. One distinct trend is the neo-Bolivarian constitutionalism, which has taken place in the ALBA countries, including the constitutional replacements of Venezuela (1999), Ecuador (2008), and Bolivia (2009). Many scholars have rightly criticized these constitutional experiments arguing that they have helped to deteriorate a liberal notion of democracy. This essay approaches a question that complements those criticisms from a different perspective: how the ALBA countries have resorted to varied notions of political representation. The authors use the classic work of Pitkin to identify the different sorts of political representation involved in the ALBA constitutional experiments, finding a combination of symbolic and descriptive representation. The former is linked to the figure of the president as a caudillo that centralizes political power, whereas the latter is fostered by both the president and the contents of the new constitutions related to the original peoples. As a result, the empowering purpose of constitutionalism has been preferred over its constraining purpose.
Keywords: authoritarianism